THE EFFECT OF TEACHING IRAQI EFL STUDENTS METACOGNITIVE LEARNING STRATEGIES ON THEIR ACHIEVEMENT IN READING COMPREHENSION (Journal of the College of Basic Education, 2022)
The present study aims to investigate the effect of teaching Iraqi EFL students metacognitive learning strategies on their achievement in reading Understanding. To accomplish the analysis goal , The next two are the Theidea is postulatedThere is no statistically meaningful variation in the mean difference between score From the reading comprehension of the experimental group and that of the control. The The latest research is limited to the fifth-grade female students / scientific branch in the Baghdad girls' preparatory and secondary schools City for During theschool year 2008-2009. It is also limited he use of Marzano’s 2001 taxonomy. The data statistically analyzed by Utilizing the t-test formula Twoindependent samples. It is detected out That a statistically relevant difference exists between the groups in favor Experimental, of the one in reading comprehension; i.e. the null hypothesis is rejected. It is concluded that the Instructional methods suggested, i.e. metacognitive Learning strategies have proven to be a beneficial technique for teaching that improves students’ ability and performance in reading comprehension. In the light of the study results, several useful recommendations concerning EFL learners, instructors, and syllabus designers were presented and several pedagogical suggestions for further research were stated